Case report: Infective endocarditis caused by Streptococcus sinensis: The first case in mainland China and literature review - Zhang, Yingmiao; Wang, Jing; Zhan, Yu; Tang, Ruizhi; Wang, Hui; Qin, Tian; Lu, Zhongxin (Frontiers in Cardiovascular Medicine, 2022)
Streptococcus sinensis was originally described as a causative agent for infective endocarditis in three Chinese patients from Hong Kong in 2002. Subsequently, several cases were reported outside Hong Kong, indicating that it is an emerging pathogen worldwide. We isolated a closely related strain in a young patient diagnosed with infective endocarditis in mainland China. In this paper, we review the course of infection and provided a comprehensive comparison of its clinical characteristics with the reported cases.